2002
DOI: 10.1161/01.res.0000022166.74073.f8
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine Kinase Activity of Discoidin Domain Receptor 1 Is Necessary for Smooth Muscle Cell Migration and Matrix Metalloproteinase Expression

Abstract: Smooth muscle cell (SMC) interactions with collagen mediate cell migration during the pathogenesis of atherosclerosis and restenosis. Discoidin domain receptors (DDRs) have been identified as novel collagen receptors. We used aortic SMCs from wild-type and DDR1؊/؊ mice to evaluate the function of the DDR1 in regulating migration. DDR1؊/؊ SMCs exhibited impaired attachment to and migration toward a type I collagen substrate. Matrix metalloproteinase-2 (MMP-2) and MMP-9 activities were concomitantly reduced in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
91
1
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 136 publications
(104 citation statements)
references
References 15 publications
9
91
1
3
Order By: Relevance
“…25 Furthermore, Ddr1 -/-SMCs exhibited reduced proliferation, migration, and MMP activity in response to type I or type VIII collagen in vitro, 25 and overexpression of DDR1 rescued these deficits. 30 In agreement with this, overexpression of DDR1 or DDR2 in human SMCs increased MMP-1 expression and decreased procollagen α 1 (I) mRNA expression. 29 Recent studies from our laboratory have demonstrated that SMC responses to collagen mediated by DDR1 may depend upon the disease context and the experimental model used.…”
Section: Collagen Remodeling Smooth Muscle Cell Proliferation and MIsupporting
confidence: 67%
“…25 Furthermore, Ddr1 -/-SMCs exhibited reduced proliferation, migration, and MMP activity in response to type I or type VIII collagen in vitro, 25 and overexpression of DDR1 rescued these deficits. 30 In agreement with this, overexpression of DDR1 or DDR2 in human SMCs increased MMP-1 expression and decreased procollagen α 1 (I) mRNA expression. 29 Recent studies from our laboratory have demonstrated that SMC responses to collagen mediated by DDR1 may depend upon the disease context and the experimental model used.…”
Section: Collagen Remodeling Smooth Muscle Cell Proliferation and MIsupporting
confidence: 67%
“…Furthermore we have shown that DDR1 is an independent favourable prognostic marker for early-stage NSCLC patients, and that mutations in DDR1 and DDR2 appear less frequently than previously reported. The collagen-binding RTKs, DDR1 and DDR2, have previously been linked to various human diseases including fibrosis (Alves et al, 1995;Mao et al, 2002;Lee et al, 2004;Avivi-Green et al, 2006), atherosclerosis (Hou et al, 2001;Hou et al, 2002;Ferri et al, 2004), and cancer (Johnson et al, 1993;Alves et al, 1995;Barker et al, 1995;Nemoto et al, 1997;Weiner et al, 2000;Dejmek et al, 2003;Ongusaha et al, 2003;Heinzelmann-Schwarz et al, 2004;Ram et al, 2006;Vogel et al, 2006). The mechanism by which DDRs may contribute to oncogenesis is as yet unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The two categories of DDRs exhibit different tissue-specific expression patterns: DDR1 is predominantly expressed in epithelial cells and DDR2 is predominantly expressed in mesenchymal cells (19,20). Previous studies have demonstrated that DDR1 and DDR2 exhibit vital functions in the regulation of fundamental cellular processes, including proliferation, survival, differentiation, adhesion and matrix remodeling (21,22). In addition, the dysregulation of DDR1 and DDR2 has been associated with a number of human diseases, including fibrotic disorders, atherosclerosis and cancer (5,23).…”
Section: Introductionmentioning
confidence: 99%